The UNDRIP and the legal significance of the right of indigenous peoples to self-determination: a human rights approach with a multidimensional perspective. Issue 1 (7th February 2019) - Cambou, Dorothée
ABSTRACT: Ten years have passed since the adoption of the UN Declaration on the Rights of Indigenous Peoples (UNDRIP) and the recognition of the right of indigenous peoples to self-determination. The declaration provides the first universal instrument to recognise and elaborate on the content of the right to self-determination for indigenous peoples. Yet, the adoption of the declaration has not solved all controversies and the implementation of the right to self-determination remains a contentious issue in practice. In this regard, the purpose of this article is to describe and analyse the legal significance of the right of indigenous peoples to self-determination as enshrined in the UNDRIP. Since the declaration emphasises the principle of territorial integrity of sovereign states, this analysis essentially focuses on the examination of what it means to claim self-determination beyond any claims for independence. In this analysis, the study argues that self-determination is based on a democratic model of self-determination that is grounded in human rights law and which calls both for the autonomy and the participation of indigenous peoples in decision-making processes that affect them. This model of self-determination is also multidimensional is so far as it includes a political, a resource and external dimensions. Ultimately, this study evidences that beyond the question of its implementation, the UNDRIP opens the pathway to significantly bolster the democratic understanding of self-determination in a manner that contributes to developing modern international law on the question of self-determination and strengten the human rights of indigenous peoples.